Anisotropy of acousto–optic figure of merit in lithium tetraborate crystals. Issue 12 (12th July 2018) - Mys, Oksana; Krupych, Oleg; Vlokh, Rostyslav
Abstract: We analyse anisotropy of acousto–optic figure of merit (AOFM) for Li2 B4 O7 crystals in order to estimate the prospects of these crystals in acousto–optics. We find that the maximal AOFM, 3.44 × 10 −15 s 3 /kg, is peculiar for the isotropic acousto–optic interaction of the incident ordinary optical wave with the quasi-longitudinal acoustic wave. For the case of anisotropic diffraction in Li2 B4 O7, the maximum 1.87 × 10 −15  s 3 /kg can be reached using the interaction of the extraordinary optical wave with the quasi-longitudinal acoustic wave. The case of collinear diffraction is characterized by small AOFMs, with the largest value 0.26 × 10 −15  s 3 /kg.